Municipality of Baghdad’s communication means and methods during imposing the law operations - Al-Shamry , Marwan Falah Hadi; Al-Shamry, Ali Jabbar (ALBAHITH ALALAMI, 2022)
This study aims at identifying how Baghdad Municipality employs public relations in law enforcement operations and the role played by the Municipality in communication and communicating with the public, raising their awareness and educating them to not abuse public property. As for the research tools, the researcher used the questionnaire as a data collection tool in addition to an analytical description of the means and methods of communication for public relations on Baghdad Municipality Facebook page. The research comes out with a set of result; the most important of which are: The means through which citizens learned about the existence of campaigns to impose the law an eliminate violations were social media platforms; they got the highest percentage among other means. emissions of the Public Relations Office of the Law Enforcement Plan (such as educating people to not violate public and private properties) were the highest among the rest of other missions. White citizens continued tracking the activities and works of the Public Relations Offices of Baghdad Municipality’s directorates, which helped them, increase their own information, the question (media channels and social networking platforms played a major role in educating people to not violate public properties) got the highest percentage.